The political economy of COVID‐19 vaccination in Indonesia - Andree Surianta; Arianto A. Patunru (Asia & the Pacific Policy Studies, 2024)
Abstract The global COVID‐19 vaccination has been marred by the problem of inequity. Low‐ and middle‐income countries (LMICs), including Indonesia, must overcome global and local barriers to provide doses to their population. Due to a lack of domestic R&D capability, Indonesia relied on global vaccine producers that are subject to the whims of their own governments. Ensuring equitable access domestically was also a challenge as public sector resources were limited. Using the four dimensions of vaccine access to examine Indonesiaʼs COVID‐19 inoculation campaign reveals gaps in the governmentʼs perception of vaccination inequity. While the administration fervently advocates for global vaccination equity, local barriers received minimal attention. Indonesiaʼs case highlights how domestic political dynamics can stymie a global effort and that resolving vaccination inequity requires lowering both global and local barriers. Finally, LMICs should also consider including private sector resources in their pandemic response to complement their limited public sector resources.